The Relationship Between Varicocele in Infertile Male and Intrauterine Insemination Success at Rumah Sakit Ibu dan Anak Puri Bunda Denpasar - Andhika Bhayangkara Putra Anak Agung Gde; I Gusti Ngurah Pramesemara; Yukhi Kurniawan; I Gusti Ayu Widianti (Universitas Airlangga, 2022)
Background: Assisted Reproductive Technology (ART), such as intrauterine insemination (IUI), can be an option for infertile couples who are expecting a pregnancy. However, the success of IUI can be influenced by various factors, one of which is varicocele. Objective: This study aims to determine the association between varicocele and IUI success. Methods: This study is an analytical cross-sectional study using patient medical records. The sample of this study was male patients aged 25-45 years with infertility and undergoing IUI in the period April to June 2021 at Rumah Sakit Ibu dan Anak Puri Bunda Denpasar. The sampling technique used, purposive sampling, was selected based on inclusion and exclusion criteria. Based on the criteria, this study selected 32 samples. Result: From 32 participants, 5 had varicocele (15.6%), and 27 were without varicocele (84.4%). In this study, we found 12 success pregnancy after IUI (37.5%), with 3 participants having varicocele (9.4%) and 9 participants without varicocele (28.1%). The chi-square analysis carried out obtained the results (p>0.05), and the calculation of the relative risk got the result (RR=0.600). Conclusion: This study showed no significant association between varicocele in infertile men and the success of IUI. The RR calculation showed that varicocele was not a risk factor for IUI failure.